Analisis Penerapan TQM dengan Pendekatan Metode Servqual di PT. Kreasi Kotak Megah - Hasibuan, Yetti Meuthia; Utama, Denny Walady; Amri, Khoirul (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Product quality is a crucial factor for companies to win the competition, both from an operational management and marketing perspective. PT Kreasi Kotak Megah Medan, a carton packaging manufacturer, faces a high level of product defects. The dominant types of defects occur in the printing and coloring processes, resulting in cost and time losses, and reduced production efficiency. Although the company has implemented Total Quality Management (TQM), production results indicate inconsistent product quality. This study aims to analyze the level of TQM implementation and formulate improvement proposals to enhance product quality. The Servqual method is used to identify gaps between expectations and performance of quality management implementation and to determine improvement priorities. The results are expected to provide an overview of the effectiveness of TQM implementation and recommendations for improvements that can improve product quality and minimize the defect rate at PT Kreasi Kotak Megah Medan.